The Fourth Industrial Revolution and Its Impact on Occupational Health and Safety, Worker's Compensation and Labor Conditions - Min, Jeehee; Kim, Yangwoo; Lee, Sujin; Jang, Tae-Won; Kim, Inah; Song, Jaechul (Safety and health at work, 2019)
The “fourth industrial revolution” (FIR) is an age of advanced technology based on information and communication. FIR has a more powerful impact on the economy than in the past. However, the prospects for the labor environment are uncertain. The purpose of this study is to anticipate and prepare for occupational health and safety (OHS) issues. In FIR, nonstandard employment will be common. As a result, it is difficult to receive OHS services and compensation. Excessive trust in new technologies can lead to large-scale or new forms of accidents. Global business networks will cause destruction of workers' biorhythms, some cancers, overwork, and task complexity. The social disconnection because of an independent work will be a risk for worker's mental health. The union bonds will weaken, and it will be difficult to apply standardized OHS regulations to multinational enterprises. To cope with the new OHS issues, we need to establish new concepts of "decent work” and standardize regulations, which apply to enterprises in each country, develop public health as an OHS service, monitor emerging OHS events and networks among independent workers, and nurture experts who are responsible for new OHS issues.